Graphene films for gas sensing applications - Hämäläinen, Joni (2013)
Gas detection at small concentrations is usually done using transition metal oxides. These semiconductors are, however, strongly dependent on parameters and conditions of growth and processing. Graphene attracts a big interest in science and technology due to its exceptional electric properties, and this truly 2-dimensional material has a great promise to be used as highly sensitive gas sensor. In this thesis, CVD and epitaxial graphene samples have been investigated in order to improve their sensitivity in gas sensing applications. The response of the sensor to different concentrations of detected gas was observed as a relative change of resistance of the sample. The aim of this study was to find optimal parameters in application of a graphene based gas sensor, and to optimize the contacting area between graphene and metal for achieving stable contacts with low resistance. Three different kinds of metal-graphene contacts and several different metals for contacting to graphene were studied. Different temperatures and humidity levels as well as irradiation with 370 nm UV-light were used to find optimal conditions for sensing NO2 gas. The sensitivity to O3 was also studied. An optimized sensor exhibited response to 20 ppb concentration of O3. In NO2 detection, the response was increased significantly by heating samples above 100 °C. In a tested epitaxial SiC sample, the resistive response to 10 ppb concentration of NO2 increased from 0.8 % in normal temperature to 1.4 % in elevated temperatures. Increasing of the temperature was also found to improve the linearity of response and to increase desorption rate of the molecules from graphene surface, allowing faster recovery after exposure. Annealed contacts with an additional graphite layer under the topmost metal layer, and with striped and dot-like geometry were found to have lower contact resistance (around 600 Ω) than a traditional contact with no additional patterning or graphite.